The impact of the information search variables, time pressure and involvement, on buying behaviour in a three-dimensional hypermedia computer-mediated environment - A. H. Nelmapius; C. Boshoff; A. P. Calitz; B. R. Klemz (South African Journal of Business Management, 2005)
The Internet has the potential (through enormous computing and data processing capabilities and the overcoming of the physical retail constraints of limited time and space) to change the way that modern-day business is being conducted. The potential of the Internet is, however, not always translated into actual retail sales.Currently product information on Web sites is mainly, with a few exceptions, of a two-dimensional nature. This study specifically investigates aspects of consumer behaviour within a three-dimensional hypermedia environment, as opposed to the two-dimensional environment. The role of a sub-set of consumer behaviour variables (time pressure and consumer involvement), as potential barriers to the more frequent use of a three-dimensional Computer-Mediated Environment (CME) as an alternative retail-shopping environment, is empirically assessed.In broad terms the objective of this study was to assess whether manipulating information availability in a CME environment influences consumers' online shopping behaviour.The results show that there is a negative relationship between shopping time pressure on the one hand and the time spent shopping on the other hand, in an Internet shopping environment without price and information displays (p 0.05); an Internet shopping environment with only price displays (p 0,01) and an Internet shopping environment with only product information displays (p 0,001). There is, however, no relationship between time pressure and consumer involvement regardless of the information available to the Internet shopper.
Keywords: 650